POTENSI GAS SERPIH FORMASI PULOBALANG, CEKUNGAN KUTAI, KALIMANTAN TIMUR - Hamdani, Ahmad; Noeradi, Dardji; Iskandar, Yusup (Bulletin of Geology, 2019)
Kutai Basin has proven to be a productive basin and has great potential, this fact indicating the existing petroleum system has been running well. Therefore, more specific investigations need to be carried out, especially for development of non-conventional hydrocarbon reserves, and find out in detail the characteristics of rocks that have potential to be carriers of potential shale gas in the Kutai Basin. The used data in this study included 5 (five) drilling wells, Ramin-1, Rasamala-1, Buat-1, Busang-1, and Murung-1 which contained wireline log data, mud logs, biostratigraphic analysis, geochemical analysis, and 81 line 2-D seismik trajectories. Further interpretation using geochemical data and modelling with Passey Method. In geomechanical data analysis, modeling used wireline logs, produce Young modulus values, Poisson ratios, and rock brittleness. Petrophysical analysis was used to be a parameter of rock quality. These data are depicted vertically and horizontally with seismic data benchmark, resulting in facies distribution and rock quality parameters as shale gas reservoirs. The research showed that Pulobalang Formation in the study area, deposited in the deltaic to slope environment, with type III kerogen, TOC content level poor until excellent with 0.12 - 7% value and brittleness value 0.05-0.971. The calculation was conducted based standard criteria as shale gas reservoir. Total potential of shale gas resources in the Pulobalang Formation reaches 2.78 TCF.